Thermal characterization of partially hydrolyzed cassava (manihot esculenta) starch granules - Lacerda, Luiz Gustavo; Azevedo, Jayme Augusto Menegassi; Carvalho Filho, Marco Aurélio da Silva; Demiate, Ivo Mottin; Schnitzler, Egon; Vandenberghe, Luciana Porto de Souza; Soccol, Carlos Ricardo (My University, 2008)
Cassava starch, partially hydrolyzed by fungal α-amylase, was characterized using thermal analysis, light microscopy and X-ray diffraction. Thermal degradation was initiated at lower degradation temperatures after enzymatic treatment and the DSC (Differential scanning calorimetry) analysis showed almost similar range of gelatinization temperature, but the enthalpies of gelatinization were quite increased for the partially hydrolyzed starch granules. The results suggested that the partial degradation of the starch granules was concentrated in the amorphous regions
Keywords: Amylase; Cassava; Hydrolysis; Thermal analysis